Identification of underlying factors of post-traumatic stress disorder in Kermanshah earthquake survivors - Xosravi, Tariq; Goudarzi, Mahmoud; Ahmadian, Hamzeh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and purpose: Earthquake is one of the most destructive and devastating natural events. The present study was conducted with the aim of identifying the underlying factors of post-traumatic stress disorder in earthquake survivors. Methods: The current research is practical in terms of its purpose and in terms of method, it is a part of sequential exploratory combined methods (qualitative-quantitative). The current research population includes all women and men who survived the Kermanshah earthquake in the cities of Salas Babajani and Sarpul Zahab located in Kermanshah province, who were exposed to the earthquake. The sample of this research was 378 earthquake victims of Sarpol Zahab and Salas Babajani cities located in Kermanshah province. The questionnaire of the underlying factors of post-traumatic stress disorder is made by the researcher and has 56 questions. The method of analysis of the present study was confirmatory factor analysis using SPSS software, version 24. Results: The results showed that the underlying factors of post-traumatic stress disorder in earthquake survivors included economic, environmental, psychological, family, social and cultural factors. The findings have shown that all factors of the questionnaire are positively correlated with each other at a significance level of 0.01. Based on this, it can be said that the factors of the questionnaire of the underlying factors of suffering from post-traumatic stress disorder had an acceptable internal correlation. Conclusion: It can be concluded that these factors can be used to predict people who will get this disease in the future.